2010
DOI: 10.1074/jbc.m110.161794
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Prion Protein in Human Urine

Abstract: The presence of the prion protein (PrP) in normal human urine is controversial and currently inconclusive. This issue has taken a special relevance because prion infectivity has been demonstrated in urine of animals carrying experimental or naturally occurring prion diseases, but the actual presence and tissue origin of the infectious prion have not been determined. We used immunoprecipitation, one-and two-dimensional electrophoresis, and mass spectrometry to prove definitely the presence of PrP in human urine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
3
12
0
Order By: Relevance
“…It is remarkable that the majority of PrP C in the urine is similar to the anchorless, N-terminally processed form observed in human and animal brains and neuronal cell models, suggesting similar processing of PrP C by kidney epithelial and cortical neuronal cells (20 -22). More importantly, the presence of PrP C in the urine of healthy individuals suggests that it is expressed on PT cells where it may provide FR activity necessary for the uptake of Tf-iron and NTBI (4,5,17).…”
Section: Prion Protein (Prpmentioning
confidence: 99%
See 1 more Smart Citation
“…It is remarkable that the majority of PrP C in the urine is similar to the anchorless, N-terminally processed form observed in human and animal brains and neuronal cell models, suggesting similar processing of PrP C by kidney epithelial and cortical neuronal cells (20 -22). More importantly, the presence of PrP C in the urine of healthy individuals suggests that it is expressed on PT cells where it may provide FR activity necessary for the uptake of Tf-iron and NTBI (4,5,17).…”
Section: Prion Protein (Prpmentioning
confidence: 99%
“…Iron transported to the cytosol is utilized for metabolic purposes, oxidized by ferritin, and stored in its shell or exported from the BL membrane by the coupled action of ferroportin and hephaestin, a ferroxidase that oxidizes exported Fe 2ϩ to Fe 3ϩ for conjugation with circulating apoTf to form diferric-Tf (Tf-iron) (4,14). Second, expression of PrP C has been described in the kidney (15,16), and significant amounts of full-length, truncated, and various glycosylated forms of PrP C are present in the urine of healthy individuals (17)(18)(19). It is remarkable that the majority of PrP C in the urine is similar to the anchorless, N-terminally processed form observed in human and animal brains and neuronal cell models, suggesting similar processing of PrP C by kidney epithelial and cortical neuronal cells (20 -22).…”
Section: Prion Protein (Prpmentioning
confidence: 99%
“…Identification and characterization of human urine PrP C using immunoprecipitation, electrophoresis, and mass spectrometry (8) demonstrated that urinary PrP C (uPrP C ) is truncated mainly at residue 112 but also at other residues up to 122. Further, uPrP C is glycosylated and carries an anchor which lacks the inositol-associated phospholipid moiety, indicating that uPrP C is probably shed from the cell surface.…”
mentioning
confidence: 99%
“…The detachment of the phospholipid moiety accounts for the paradoxical slower migration of PI-PLC-digested PrP C species under SDSpolyacrylamide gel electrophoresis (9). Expectedly, this effect is not observed upon PI-PLC treatment of native and recombinant anchorless PrP C molecules (10) and of post-translational modified PrP C species lacking the phospholipid component (8). On the other hand, in vitro studies have shown that anchorless PrP C is not tethered to the cell membrane, and is not recycled within the endosomal compartment, being instead secreted extracellularly (11).…”
mentioning
confidence: 99%
“…Posttranslational PrP C processing involves endosomal recycling of the cell surface full-length protein and proteolytic cleavages at residues 111/112 and ϳ90, leading to the generation of N-terminally truncated C1 and C2 fragments (5); an additional proteolytic cleavage of PrP C is thought to occur at the C terminus, near the GPI-anchor, which results in detachment of the fulllength protein from the cellular surface. Even though the bulk of brain PrP C is GPI-anchored, protease-mediated shedding of the PrP C ectodomain or enzymatic cleavage of the GPI phospholipid moiety have been reported in the cerebrospinal fluid (CSF), plasma, urine, and cell cultures (6,7,8). However, physiologically shed PrP C species display distinct features from PrP C experimentally exposed to the enzyme phosphatidylinositol-* This work was supported in part by RF2009-1474758 (to G.…”
mentioning
confidence: 99%